Konsep Pertanggungjawaban Pidana Bagi Perlindungan Anak Yang Berhadapan Dengan Hukum - Diah Sulastri Dewi (Jurnal Penelitian Hukum Legalitas, 2020)
The deradicalization program is a program mandated by Law Number 5 of 2018 which is carried out in coordination with government institutions or institutions with targets being carried out on suspects, defendants, convicts, prisoners, ex-terrorism convicts, and people or groups who have been exposed to radical terrorism. The normative legal research method in this research used a methodological approach that is applied, namely the legal approach, conceptual approach, historical approach, and philosophical approach. Based on the results of this research that the application of the concept of deradicalization to perpetrators of criminal acts of terrorism in Indonesia since the issuance of Presidential Decree number 46 of 2010 concerning the National Agency for Combating Criminal Acts of Terrorism has been running but in the implementation of the deradicalization program it has not touched the substance of the root of the problem, namely efforts to stem the rate of rad[1]icalism. Deradicalization model that prioritizes reintegration such as counter terrorism, preventing radicalism, understanding comparisons, avoiding hate provocations, hostility in the name of religion, preventing people from being indoctrinated, and community participation rejecting terrorism.